The Flexible Feminine in Vietnam: ‘Ordinary’ Goddesses and Extraordinary Ethnography - Lilley, Rozanna (The Australian journal of anthropology, 2006)
Book reviewed in this article: Philip Taylor. Goddess on the Rise: Pilgrimage and Popular Religion in Vietnam